Principles of Sustainable Development of Businesses on the Adaptive Lifecycle Dimension of Connectedness - Sriram, K.; Ganesh, L.S.; Madhumathi, R. (European Journal of Sustainable Development, 2013)
The Panarchy model of ecological systems and analogically business systems identifies 3dimensions of sustainability over the adaptive life cycle of a system. Principles on thesecond dimension of the Panarchy model, namely connectedness, are discussed in thispaper. These principles relate to processes, networks and controls of ecological systemsand analogically business systems. Examples of operation of these principles in thebusiness context are given.